Impact of Gas Hydrates and Long-Term Operation on Fatigue Characteristics of Pipeline Steels. (2017) - Poberezhny, Lyubomyr; Maruschak, Pavlo; Hrytsanchuk, Andrij; Poberezhna, Liubov; Prentkovskis, Olegas; Stanetsky, Andrij
Abstract: Fatigue tests of specimens from pipe steel 17GS and steel 20 after exposure to gas hydrates are performed. A decrease in lifetime was found to be from 15 to 25%, and given the degradation of the material it was 2.5 times more, indicating the need to consider the hydrated factor in assessing the residual life. Based on the results of fracture toughness tests, a critical crack size was identified for specimens from steel 20. It is shown that the critical crack size decreases by 21% for the pipes after 31 years of operation. The yield stress of test specimens was defined by the proposed method. The results are generally consistent with the industrial practice, the yield stress decreased only slightly over the entire service lifetime.